Controlled Environment Agriculture for sustainable development: A call for investment and innovation - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2021)
Controlled Environment Agriculture (CEA) is the production of plants, fish, insects or animals inside structures, such as greenhouses and buildings, in controlled conditions. In a rapidly urbanizing world, CEA can contribute to sustainable development, e.g. through reduced use of land, water and inputs. There is a need for innovation in policy, technology and business practices to scale up CEA in the Global South sustainably and equitably.